Intra‐aortic balloon counterpulsation pump in heart failure patients during MitraClip implantation—A propensity‐score matched analysis. Issue 7 (30th September 2018) - Keßler, Mirjam; Seeger, Julia; Wöhrle, Jochen; Rottbauer, Wolfgang; Markovic, Sinisa
Abstract: Objectives: To analyze 30‐day and 6‐month results after percutaneous mitral valve repair using an IABP as circulatory support. Background: The use of intra‐aortic balloon counterpulsation pump extended the spectrum of cardiovascular interventions. Methods: Since 2014, 17 patients of 365 patients (4.7%) at our center received an IABP during MitraClip implantation procedure. We compare the periprocedural results to a control group of 17 patients treated with MitraClip without an IABP support. To adjust for differences of baseline characteristics a propensity‐score matching for age, baseline blood pressure, preoperative EuroSCORE II and left ventricular ejection fraction was performed. The decision for prophylactic implantation of an IABP was at the discretion of the interventionalist. For both groups, clinical results up to 6 months were evaluated. Results: The IABP group had higher NT‐pro BNP levels at baseline and increased left ventricular diameters. The procedure was more often categorized as "urgent" due to refractory heart failure in the IABP group. All procedures were carried out successfully, thereby achieving a sufficient MR reduction in both groups. Length of hospital stay was significantly longer in the IABP group 11.7 ± 14 days (compared to 6.5 ± 2.9 days in the No IABP group, P  < 0.01). All patients in both groups had an event‐free 30‐day follow‐up. MACCE rate was higher in the IABP group compared to the No IABP group (47.1% vs. 23.5%, P = 0.14). Conclusion: Insertion of an IABP during MitraClip procedure might be a feasible option to achieve comparable results and may provide additional safety and procedural hemodynamic stability in the setting of high‐risk percutaneous mitral valve repair.